Spatial Competition and the Core - Hamilton, J. H.; MacLeod, W. B.; Thisse, J.-F. (Quarterly Journal of Economics, 1991)
Journal Article Spatial Competition and the Core Get access Jonathan H. Hamilton, Jonathan H. Hamilton University of Florida Search for other works by this author on: Oxford Academic Google Scholar W. Bentley MacLeod, W. Bentley MacLeod Universite de Montreal Search for other works by this author on: Oxford Academic Google Scholar Jacques-François Thisse Jacques-François Thisse CORE and Virginia Polytechnic Institute Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 106, Issue 3, August 1991, Pages 925–937, https://doi.org/10.2307/2937934 Published: 01 August 1991